2012
DOI: 10.4102/sajip.v38i2.996
|View full text |Cite
|
Sign up to set email alerts
|

The Robben Island diversity experience. An exploration of South African diversity dynamics

Abstract: Orientation: Because of its historic, symbolic and psychological representation, presenting a diversity event on Robben Island posed invaluable opportunities to form an in-depth understanding of South African diversity dynamics. This research focussed on such an event interpreted from the systems psychodynamic perspective.Research purpose: The purpose of the research was to describe the experiences of participants attending the Robben Island Diversity Experience (RIDE) in order to understand South African dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…It appears that the conscious feelings, namely of feeling disempowered, baffled, disqualified, hurt and negated, experienced by the lecturers in the face of the accusations of racism by students, might attest to their sense of being denigrated by the (Black) students and management (see Pretorius, 2003;Skolnick & Green, 2004). The lecturers probably also experienced that the students and management, by projecting a racist identity onto them, perceived them to continue the racism and discrimination of the apartheid regime, specifically as the Vlakplaas of the university, against the (Black) students and management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears that the conscious feelings, namely of feeling disempowered, baffled, disqualified, hurt and negated, experienced by the lecturers in the face of the accusations of racism by students, might attest to their sense of being denigrated by the (Black) students and management (see Pretorius, 2003;Skolnick & Green, 2004). The lecturers probably also experienced that the students and management, by projecting a racist identity onto them, perceived them to continue the racism and discrimination of the apartheid regime, specifically as the Vlakplaas of the university, against the (Black) students and management.…”
Section: Discussionmentioning
confidence: 99%
“…It affords us the opportunity to attend to unconscious phenomena within people, the organisational context (tasks, structures, boundaries) and the complex interaction between the two (Amado, 1995;Nutkevich, 1998). In diversity dynamics the theoretical underpinnings of SP are applied to understand the psychodynamics which occur in the context of difference and similarities amongst people (Cilliers & May, 2002;May & Evans, 2004;Pretorius, 2003).…”
Section: The Systems Psychodynamic Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, legislation on employment equity and affi rmative action brought a unique kind of competition for economic and emotional survival into the workplace (Cilliers & Stone, 2005). In some organizations, the intolerances for the differences led to discomfort, disrespect and strong feelings of racial fear, anger, resentment, confl ict, competition, hurt, hopelessness and helplessness amongst employees (Cilliers & May, 2002;Pretorius, 2003). Managing diversity effectively relates to how managers can facilitate harmonious relationships between different people (Cilliers & Terblanche, 2010), through cognitive understanding and the experience of emotional meaning making (Watts, 2009).…”
Section: Diversity and Individual Diversity Managementmentioning
confidence: 99%
“…how individual managers experience diversity situations intra-and interpersonally. The diversity literature indicates that the effective management of such diversity situations depends on the managers ' level of psychological functioning (Booysen, 2005;Pretorius, 2003). No research could be found investigating managers ' diversity experiences in this context.…”
Section: Introductionmentioning
confidence: 99%